Explanation:
For y=g(x) and y = f(x), we can set f(x) = g(x) and go from there.
Here, we simply subtracted 8 from both sides
Next, we can substitute u in for 2^x to get
4 * (1/u) - 5 = -u
4/u - 5 = -u
Multiply both sides by u
4 - 5u = -u²
Add u² to both sides
u² -5u +4 = 0
Factor
(u-4)(u-1) = 0
We now know that our solutions to this are u = 4 and u = 1, so we must figure out when 2^x = 4 and 2^x = 1. We can then figure out that 2² = 4 and 2^0 = 1, so our answers are 2 and 0 for the second question.
For the first, we can simply plug 2 and 0 into f(x) to get (2,4) and (2,7) as our answers